A OFERTA DE SERVIÇOS JURÍDICOS À COMUNIDADE MIGRANTE INTERNACIONAL EM CORUMBÁ: O CASO DO ESCRITÓRIO MODELO DE ASSISTÊNCIA JUDICIÁRIA, DO CAMPUS PANTANAL NA UNIVERSIDADE FEDERAL DE MATO GROSSO DO SUL - Renata Calixto de Moura (2022)
From the observation of daily life in Brazil-Bolivia in Corumbá, located in Mato Grosso do Sul, with special attention to local migratory flows, the interest in developing this research arose. The offer of legal services in the legal field of the Pantanal of the Federal University of Mato Grosso do Mato Grosso to the international migrant community of the Office of Judicial Assistance of the Pantanal of the Federal University of Mato Grosso, given the lack of support to internationals. These, sometimes, their peculiarities, certain characteristics as subjects without rights of extralegal migration, in particular, are valid from the perspective of international migrations supported by current legal concepts when understanding the legal condition of migrations, especially in terms of extension, from the perspective of international migration vulnerabilities in face of the constant migration scenario. At the end of the partnership access to the union, the offer of legal services proposed with the proposal of international justice and content as a public means of international poverty defense.